Efektivitas Program Pencegahan dan Pengentasan Generasi Bebas Stunting (P2GBS) Melalui Edukasi Gizi Seimbang pada Murid TK Dharma Wanita di Desa Sumberjambe - Dewi Rokhmah; Khusnul Hidayati; Rista Dwi Hermilasari (Pendidikan Fisika FKIP UNEJ, 2022)
The main health problem in Sumberjambe is stunting. This is known from the prevalence of stunting under five, which is 80.8%, so a health program is needed such as P2GBS (Prevention and Alleviation of Stunting-Free Generations) which includes balanced nutrition education activities. This study aims to analyze the effectiveness of balanced nutrition education activities in Sumberjambe Village in the P2GBS (Prevention and Alleviation of Stunting-Free Generation) program through activities. Balanced nutrition education activities are carried out using the socialization method of discussions and cooking demonstrations using posters containing my plate, booklets on preventing stunting, emodemo modules, lunchboxes with balanced nutrition stickers, powerpoints, and pre-test and post-test sheets with the target being students of Dharma Wanita Sumberjambe Kindergarten. . The results of this study found three priority problems that cause stunting, including low family economy, parenting patterns for consumption in infants, many couples of childbearing age are too young. Based on the priority issues, the P2GBS program was carried out in which there were activities including balanced nutrition education. The activities carried out showed that there was an increase in target understanding of balanced nutrition education by 9.43% with pre-test results of 67.99% and post- test of 77.42% where the activity has an effectiveness result of >1 so that the program is effectively carried out to help reduce the prevalence of stunting in Sumberjambe Village.